Clinical and epidemiological characteristics of Guillain-Barré syndrome during the 2019 outbreak in a hospital in Chiclayo, Peru - Cueva Ortega, Lisbeth (2025)
The objective is to describe the clinical and epidemiological characteristics of Guillain-Barré syndrome (GBS) during the 2019 outbreak in patients treated in a hospital in Chiclayo, Lambayeque, Peru. This is a descriptive and retrospective study conducted on 36 cases. Data were collected through a documentary analysis of clinical-epidemiological surveillance research forms for GBS, provided by the Ministry of Health. The sample was characterized by a median age of 46.05 years, a predominance of male sex (69.40 %) and an origin from Lambayeque (66.70 %). Additionally, 19.40 % of patients had chronic diseases, and the most frequent conditions found in their medical history were respiratory infections (45.50 %) and gastrointestinal infections (36.40 %). The clinical presentation was characterized by weakness (97.20 %), ascending paralysis (72.20 %), paresis of the left facial nerve (8.30 %), hyporeflexia (91.70 %) and decreased muscle tone (47.20 %). We conclude that male sex, an age between 30 and 59 years and a history of gastrointestinal and respiratory infections were the predominant epidemiological characteristics of GBS in this outbreak; while weakness, ascending paralysis, pain and hyporeflexia were among the most common clinical characteristics. Active surveillance and the strengthening of preventive and care capacities for this disease are recommended.